2010
DOI: 10.5032/jae.2010.02036
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Agricultural Agents’ Decisions to Remain in an Extension Career

Abstract: This qualitative study sought to explore and describe why Florida agricultural agents remained in an extension career. A purposive sample was used to select twelve agents who were classified into one of the three stages of the career stages model (Kutilek, Gunderson, & Conklin, 2002). In-depth interviews were used to investigate positive and negative influences that affected agents' decisions. Grounded theory was used as the primary data analysis method (Strauss & Corbin, 1998). Seven selective codes emerged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Next, the negative association between burnout and work engagement was larger and stronger than the relationship between burnout and turnover intention. This is a remarkable finding that aligns with the work of Arnold and Place (2010). They assert that educators strongly identify with their work and find it meaningful.…”
Section: Discussionsupporting
confidence: 57%
“…Next, the negative association between burnout and work engagement was larger and stronger than the relationship between burnout and turnover intention. This is a remarkable finding that aligns with the work of Arnold and Place (2010). They assert that educators strongly identify with their work and find it meaningful.…”
Section: Discussionsupporting
confidence: 57%
“…Cooperative Extension according to Extension Committee on Organization andPolicy (2002, 2005). Arnold, Place, Osborne, Israel, & Tenbroeck (2008), found that the six categories that influenced agents' decisions to enter Extension were: agent background, career contacts, service to the agricultural community, nature of Extension work, position fit, and university supported education. In order for Cooperative Extension to continue being agile and flexible, Extension must focus on long term employment (Extension Committee on Organization and Policy, 2002).…”
Section: Recruitment and Retention Are Two Of The Top Internal Issuesmentioning
confidence: 99%
“…Extension administrators must thoroughly examine how to employ competent, long term staff, to ensure the longevity of the program (Arnold & Place, 2010).…”
Section: Safrit and Owenmentioning
confidence: 99%
See 1 more Smart Citation
“…The sustained success and longevity of Extension professionals who are based in local communities through local government partnerships has been documented over the past 50 years (Arnold & Place, 2010;Baker & Hadley, 2014;Clegg, 1967;Forstadt & Fortune, 2016;Fourman & Jones, 1997;Harder et al, 2014;Hyatt, 1966;Lindner, 1998;Martin & Kaufman, 2013;Morrill & Morrill, 1967). Herzberg et al's (1959) Motivation-Hygiene theory identified that things unrelated to job responsibilities (hygiene factors) caused dissatisfaction that may result in a desire to separate.…”
Section: Introduction and Problem Statementmentioning
confidence: 99%